Training Report on Political Economy for ‘Strengthening Adaptive Capacity of Extensive Livestock Systems for Food and Nutrition Security and Low-emissions Development in Eastern and Southern Africa’ Project - Sinyangwe, Sulwilanji; Makonnen, Brook T. (International Livestock Research Institute, 2024)
This report details the virtual training session on political economy, held on 31 May 2024, under the "Strengthening Adaptive Capacity of Extensive Livestock Systems for Food and Nutrition Security and Low-emissions Development in Eastern and Southern Africa" project. It provides insights into the session's objectives, key content, discussions, emerging issues, and recommendations for future actions. The training session, facilitated by Dr. Chrispen Sukume, an agricultural economist from the Livestock and Meat Advisory Council of Zimbabwe, focused on political economy analysis within the context of livestock systems. The session aimed to enhance participants' understanding of the interaction between political and economic processes and their impact on livestock policies and interventions.